Formal demonstration of the independence on the optical activity of the maximum gain position in a two-wave coupling experiment - Gómez, Jorge Alberto; Salazar, Ángel (Photonics Letters of Poland, 2010)
The two-beam coupling method has been a useful procedure to estimate the screening Debye length in a photorefractive crystal. The position and value of the maximum gain value as a function of the photorefractive spacing grating is used to obtain the Debye length value. This position and not the maximum value of the gain, appears to be evidently independent of the optical activity of the material. However, a formal treatment to this effect is not found in the specialized literature. In this paper, we present such formal treatment. Full text: PDF References: J.A. Gómez, H. Lorduy, Á. Salazar, "Novel procedure for the simultaneous determination of the Debye length and electro-optic coefficient for an optically active photorefractive Bi12SiO20 crystal", Opt. Commun. 284, 460 (2011). [CrossRef] J. Frejlich, Photorefractive Materials, Fundamental Concepts, Holographic recording and Materials Characterization (John Wiley & Sons, Inc. USA 2007). R.W. Mullen, in: P. Günter and J.-P. Huignard (Eds.), Photorefractive Materials and Their Applications I, Fundamental Phenomena (Springer-Verlag, Berlin 1988). P.A.M. dos Santos, P.M. Garcia, J. Frejlich, "Transport length, quantum efficiency, and trap density measurement in Bi12SiO20", J. Appl. Phys. 66, 247 (1989). [CrossRef] L. Arizmendi, "Simple holographic method for determination of Li/Nb ratio and homogeneity of LiNbO3 crystals", J. Appl. Phys. 64, 4654 (1988). [CrossRef] P. M. Garcia, L. Cescato, J. Frejlich, "Phase-shift measurement in photorefractive holographic recording", J. Appl. Phys. 66, 47 (1989). [CrossRef] J. Frejlich, P. M. Garcia, L. Cescato, "Adaptive fringe-locked running hologram in photorefractive crystals", Opt. Lett. 14, 1210 (1989). [CrossRef] J. Frejlich, P. M. Garcia, L. Cescato, "Adaptive fringe-locked running hologram in photorefractive crystals: errata", Opt. Lett. 15, 1247 (1990). [CrossRef] D.J. Webb, L. Solymar, "The effects of optical activity and absorption on two-wave mixing in Bi12SiO20", Opt. Commun. 83, 287 (1991). [CrossRef] S. Bian, J. Frejlich, "Actively stabilized holographic recording for the measurement of photorefractive properties of a Ti-doped KNSBN crystal", J. Opt. Soc. Am. B. 12, 2060 (1995). [CrossRef] A.A. Freschi, P.M. Garcia, J. Frejlich, "Charge-carrier diffusion length in photorefractive crystals computed from the initial hologram phase shift", Appl. Phys. Lett. 71, 2427 (1997). [CrossRef] I. de Oliveira, J. Frejlich, "Dielectric relaxation time measurement in absorbing photorefractive materials", Opt. Commun. 178, 251 (2000). [CrossRef] I. de Oliveira, J. Frejlich, "Photorefractive running hologram for materials characterization", J. Opt. Soc. Am. B 18, 291 (2001). [CrossRef] L. Mosquera, I. de Oliveira, J. Frejlich, "Dark conductivity, photoconductivity, and light-induced absorption in photorefractive sillenite crystals", J. Appl. Phys. 90, 2635 (2001). [CrossRef] I. de Oliveira, J. Frejlich, "Gain and stability in photorefractive two-wave mixing", Phys. Ver. A 64, 033806 (2001). M.C. Barbosa, L. Mosquera, J. Frejlich, "Speed and diffraction efficiency in feedback-controlled running holograms for photorefractive crystal characterization", Appl. Phys. B, 72, 717 (2001). [CrossRef] M.C. Barbosa, J. Frejlich, "Photorefractive fringe-locked running hologram analysis in three-dimensional space", J. Opt. A: Pure Appl. Opt. 5, S416 (2003). [CrossRef] I. de Oliveira, J. Frejlich, "Diffraction efficiency measurement in photorefractive thick volume holograms", J. Opt. A: Pure appl. Opt. 5, S428 (2003). [CrossRef] R. Montenegro, A.A. Freschi, J. Frejlich, "Photorefractive two-wave mixing phase coupling measurement in a self-stabilized recording regime", J. Opt. A.: Pure Appl. Opt. 10, 104006 (2008). [CrossRef] A. Salazar, H. Lorduy G., R. Montenegro, J. Frejlich, "An improved procedure for fringe-locked photorefractive running hologram data processing", J. Opt. A: Pure appl. Opt. 11, 1 (2009). [CrossRef] A. Shumelyuk, M. Wesner, M. Imlau, S. Odoulov, "Wave mixing in nominally undoped Sn2P2S6 at high light intensities", Appl. Phys. B 95, 497 (2009). [CrossRef]